2017
DOI: 10.1111/bcpt.12870
|View full text |Cite
|
Sign up to set email alerts
|

Proximal Neuropathy and Associated Skeletal Muscle Changes Resembling Denervation Atrophy in Hindlimbs of Chronic Hypoglycaemic Rats

Abstract: Peripheral neuropathy is one of the most common complications of diabetic hyperglycaemia. Insulin-induced hypoglycaemia (IIH) might potentially exacerbate or contribute to neuropathy as hypoglycaemia also causes peripheral neuropathy. In rats, IIH induces neuropathy associated with skeletal muscle changes. Aims of this study were to investigate the progression and sequence of histopathologic changes caused by chronic IIH in rat peripheral nerves and skeletal muscle, and whether such changes were reversible. Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…We now show that increased GV and TBR were associated with small nerve fiber damage evidenced by lower CNBD in patients with type 1 and type 2 diabetes. We believe the underlying mechanisms of nerve damage are very different from the severe insulin-induced experimental hypoglycemic neuropathy characterized by reduced motor and sensory nerve conduction velocities and a distal dying back axonal degeneration affecting motor more than sensory axons ( 40 ) and axonal degeneration ( 41 ) in the proximal sciatic rather than distal plantar nerves ( 42 ), with myelinated nerve fiber damage ( 43 ) in motor rather than sensory roots ( 44 ). Indeed, in a study of diabetic BB rats with insulin implants to induce moderate hypoglycemia, there was evidence of shorter and thinner intraepidermal nerve fibers ( 45 ).…”
Section: Discussionmentioning
confidence: 98%
“…We now show that increased GV and TBR were associated with small nerve fiber damage evidenced by lower CNBD in patients with type 1 and type 2 diabetes. We believe the underlying mechanisms of nerve damage are very different from the severe insulin-induced experimental hypoglycemic neuropathy characterized by reduced motor and sensory nerve conduction velocities and a distal dying back axonal degeneration affecting motor more than sensory axons ( 40 ) and axonal degeneration ( 41 ) in the proximal sciatic rather than distal plantar nerves ( 42 ), with myelinated nerve fiber damage ( 43 ) in motor rather than sensory roots ( 44 ). Indeed, in a study of diabetic BB rats with insulin implants to induce moderate hypoglycemia, there was evidence of shorter and thinner intraepidermal nerve fibers ( 45 ).…”
Section: Discussionmentioning
confidence: 98%
“…Histopathology was observed by double blinding using an Olympus microscope with a magnification of 400x. Assess the degree of histopathological damage to the sciatic nerve using the Jensen et al, (2018) method. Data were analyzed using the Kruskal-Wallis test and continued with the Mann-Whitney test, with a significance level of 95% (α=0.05), with a p-value of <0.05 considered significant.…”
Section: Methodsmentioning
confidence: 99%
“…Rats were sacrificed using the cervical dislocation method, and the right sciatic nerve was taken for histopathological observation. Assessment of the degree of ischiatic nerve histopathological damage is using the Jensen et al, (2018) method. Data were analyzed using the Kruskal-Wallis test and continued with the Mann-Whitney test.…”
mentioning
confidence: 99%
“…In recent years, DPN patients have often been associated with proximal nerve involvement. In the study of Jensen et al [10], hypoglycemia caused by insulin intervention in DPN rats was found to accelerate peripheral neuropathy, and the incidence of SN axonal degeneration was higher, while the possibility of plantar nerve abnormality was lower. However, with the extension of intervention time, the incidence of peripheral degeneration of SN and plantar nerve was equivalent.…”
Section: Introductionmentioning
confidence: 94%
“…Currently, the clinical treatment of DPN mainly involves neuronutrition and blood circulation improvement on the basis of blood glucose control, which can only temporarily alleviate the progression of the disease with unsatisfactory results [12]. As medical research advances, molecular targeted therapy has become a research hotspot with remarkable progress achieved in the treatment of malignant tumors, providing a new direction for the research of DPN [10]. Therefore, finding effective intervention targets for DPN is an urgent problem for medical workers.…”
Section: Introductionmentioning
confidence: 99%